A PANCASILA AND EDUCATIONAL ANALYSIS OF THE GOVERNMENT'S FREE NUTRITIOUS MEAL PROGRAM - Melisa, Melisa; Hendra, Hendra; Razak, Ahmad Zabidi Abdul (SYNTIFIC, 2025)
Background. The Government’s Free Nutritious Meal Program represents a strategic public policy aimed at improving children’s nutritional status while supporting human resource development in Indonesia. Research Purpose. This study aims to review the implementation of the Free Nutritious Meal Program from the perspectives of education and Pancasila values. Research Method. Using a qualitative approach through a literature review and case study. The analysis focuses on how the program reflects the principles of Pancasila, particularly social justice, humanity, cooperation, and equitable access to education. Findings. The Free Nutritious Meal Program contributes positively to students’ learning concentration, school participation, and educational equity, especially among vulnerable and disadvantaged groups. From a Pancasila perspective, the program embodies the values of social justice and collective responsibility by ensuring equal nutritional access for students across regions. However, challenges remain in terms of program sustainability, quality control, and inter-sectoral coordination. Conclusion. The Free Nutritious Meal Program has strong relevance to educational development and the implementation of Pancasila values, provided that continuous evaluation and policy refinement are carried out to ensure its effectiveness and long-term impact.